PENGARUH KOMPETENSI PEDAGOGIK GURU DAN SERTIFIKASI GURU TERHADAP KINERJA GURU SD/MI DI KECAMATAN PETARUKAN KABUPATEN PEMALANG - Akhmad Zaeni; Ghufron Abdullah; Ngasbun Egar (Jurnal Manajemen Pendidikan (JMP), 2016)
The purpose of this study are: (1) to determine the significance of the influence of pedagogical competence of teachers on the performance of teachers of SD/MI in the UPP District of Petarukan Pemalang, (2) to determine whether there is influence of teacher certification on teacher performance SD/MI in the region UPP District of Petarukan Pemalang, (3) to determine whether there is the influence of pedagogical competence of teachers and certified teachers on teacher performance SD/MI in the territory of the District UPP Petarukan Pemalang.The population in this study were all teachers SD/MI in District Petarukan Pemalang already qualified certification as 313 people. After the calculated obtained sample of 175 people by using proportional random sampling technique. Data collection methods used were questionnaires / questionnaire. Analysis of the data used is descriptive analysis, test requirements and test hypotheses include simple linear regression analysis and multiple regression analysis and test of determination (R2).Hypothesis test results show that: 1) there is a significant and positive influence Pedagogic Competence (X1) on the Performance of Teachers (Y) SD/ MI in the territory of the District UPP Petarukan Pemalang. This is evident from the test results of t test partial values obtained tcount amounted to 4.635 greater than ttable 1.974 (4.635 > 1.974), 2) there is a positive influence and significant Teacher Certification (X2) on Teacher Performance SD/MI in the UPP District of Petarukan Pemalang. This is evident from the test results of t test partial obtained tcount amounted to 4.617 greater than ttable 1.974 (4.617> 1.974), and 3) there is a positive influence and significant Competence Pedagogy (X1) and the Teacher Certification (X2) the performance of teachers (Y) SD / MI in the territory of the District UPP Petarukan Pemalang. This is evident from the results of hypothesis testing simultaneous F test values obtained Fhitung 10.720 3.0485 greater than F table (10.720> 3.0485).